2013
DOI: 10.1371/journal.pone.0055905
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure during Adulthood Alters Expression of Aromatase and 5α-Reductase Isozymes in Rat Prostate

Abstract: The high incidence of prostate cancer (PCa) and benign prostatic hypertrophy (BPH) in elderly men is a cause of increasing public health concern. In recent years, various environmental endocrine disruptors, such as bisphenol A (BPA), have been shown to disrupt sexual organs, including the prostate gland. However, the mechanisms underlying these effects remain unclear. Because androgens and estrogens are important factors in prostate physiopathology, our objective was to examine in rat ventral prostate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 48 publications
5
58
0
3
Order By: Relevance
“…Therefore, our present demonstration of BPA stimulation of aromatase expression may have significant implications for the function of estrogens during pregnancy. Although our present findings are in contrast to those reported previously of decreased aromatase activity and expression in JEG-3 cells [33,35], they are consistent with those of numerous in vitro and in vivo studies [48][49][50][51][52][53][54][55]. For example, BPA exposure has been shown to increase aromatase expression in the rat brain [50,53], ovary [51] and prostate [54].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our present demonstration of BPA stimulation of aromatase expression may have significant implications for the function of estrogens during pregnancy. Although our present findings are in contrast to those reported previously of decreased aromatase activity and expression in JEG-3 cells [33,35], they are consistent with those of numerous in vitro and in vivo studies [48][49][50][51][52][53][54][55]. For example, BPA exposure has been shown to increase aromatase expression in the rat brain [50,53], ovary [51] and prostate [54].…”
Section: Discussionsupporting
confidence: 87%
“…The decrease in anogenital distance in our highest BPA treatment (3000 lg/kg/day) may be explained by reduced available serum testosterone or an increase in aromatase expression and/or activity, as mentioned previously by Quignot et al (2012). There is some evidence for effects of BPA at the androgen receptor (AR) (Vinggaard et al 2008), which may be due the down regulation of 5-areductase expression in mice BPA treated during the development (Castro et al 2013;Liu et al 2015). Reduced 5-a-reductase expression reduces the dihydrotestosterone levels and elevates plasma estradiol levels.…”
Section: Discussionsupporting
confidence: 65%
“…Protein concentration was determined using Bio-Rad DC⨵ assay reagent (BioRad Laboratories) with Protein assay standard II (Bovine serum albumin, Bio-Rad) as the standard. Aliquots of samples were subjected to 12% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), western blot and antibodies incubation following Castro et al (2013a). Primary antibody concentration was rabbit anti-5α-R2 (Santa Cruz sc-20659), 1:100; rabbit anti-5α-R3 (Novus Biologicals NBP1-69612), 1:1000.…”
Section: Electrophoresis and Western Blot Analysismentioning
confidence: 99%
“…Our previous findings indicated that adult exposure to BPA decreases the expression of 5α-R isozymes type 1 and type 2 in the prostate of rats (Castro et al, 2013a). In contrast, BPA failed to modify 5α-R expression in the prefrontal cortex (PFC) of adult (Castro et al, 2013b) or juvenile (Castro et al, 2015) male rats.…”
Section: Introductionmentioning
confidence: 99%